(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Human papillomavirus (HPV) is a sexually transmitted virus found in virtually all cases of cervical cancer that kills 275,000 women every year and is the biggest contributor to years of life lost from cancer among women in the developing world. Objectives: To determine barriers to HPV vaccination and cervical cancer prevention at the health personnel level in low-resource settings. To evaluate the performance of cervical cancer secondary prevention tools. To identify barriers and facilitators associated with the administration of the full HPV vaccination regimen. Methods: 150 HIV-infected women underwent conventional Papanicolaou (Pap) smear, visual inspection with acetic acid (VIA), colposcopy, and biopsy. Region under curve analysis was conducted to compare the accuracies between VIA and Pap smear. 9600 doses of GARDASIL vaccines were administered to girls in Western Kenya targeting girls aged 9-14 years. A cross-sectional survey of health care providers was also conducted. Results: VIA had a sensitivity of 69.6% (CI=55.1–81.0%), specificity of 51.0% (CI=41.5–60.4%), positive predictive value (PPV) of 38.6% (CI=28.8–49.3%), and negative predictive value (NPV) of 79.1% (CI=67.8–87.2%). For conventional Pap smear, sensitivity was 52.5% (CI=42.1–71.5%), specificity 66.3% (CI=52.0–71.2%), PPV 39.7% (CI=27.6–51.8%), and NPV 76.8% (CI=67.0–85.6%). 1933 of 3026 (63.8%) girls received a second HPV dose, whereas 1182 of 3026 (39.1%) received a third dose. 71.8% of girls had a female guardian and 28.1% had a male guardian. The median time lapse between the first and third doses was 175 days (IQR: 168-182). High level of divergence between knowledge of HPV infection and vaccines with a mean score of 2.27 indicating a negative attitude among health care workers. 36.8% expressed concern that the HPV vaccine may result in promiscuity. Conclusions: Lack of proximity to vaccination centers requires an innovative vaccine delivery strategy. More education of caregivers undergoing cytological screening to raise awareness of the importance of HPV vaccination.